Litteraturanmeldelse – Approaches to Algebra Perspectives for Research and Teaching - Breiteig, Trygve (NOMAD Nordic Studies in Mathematics Education, 1997)
Bednarz, N., Kieran, C. & Lesley, L. (eds.) (1996) Approaches to Algebra. Perspectives for Research and Teaching. (Mathematics Education Library, Volume 18). Dordrecht, NL: Kluwer Academic Publishers, 345 p. https://doi.org/10.1007/978-94-009-1732-3_1